Dietary supplementation of delta-aminolevulinic acid to lactating sows improves growth performance and concentration of iron and hemoglobin of suckling piglets - LEE, S I; LI, T S; KIM, I H (The Indian Journal of Animal Sciences, 2016)
To confirm whether dietary supplementation of delta-aminolevulinic acid (δ-ALA) to lactating sow improves iron concentration of suckling piglets, 24 gestating sows [(Yorkshire × Landrace), before 14–day of farrowing] and their litters were evaluated on growth performance, blood characteristics, and milk composition. Dietary treatments were as follows: (i) CON, corn-soybean meal based diet; (ii) CON + 0.05 % δ-ALA; and (iii) CON + 0.1 % δ-ALA. Lactating sows fed with δ-ALA had increased backfat thickness and decreased backfat thickness at weaning. Also, dietary supplementation of δ-ALA increased protein concentration in the milk of lactating sows (linear). In addition, lactating sows fed with δ-ALA had increased BW (linear), ADG (linear), iron (linear), and hemoglobin (linear) concentration in suckling piglets. Based on the results, we suggested that dietary supplementation of δ-ALA to lactating sows improved growth performance and concentration of iron and hemoglobin in blood of suckling piglets. Also, dietary supplementation of δ-ALA had positive effects on backfat thickness and protein concentration in milk of lactating sows.